2019
DOI: 10.1039/c9cp01267b
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical characterization of new and efficient synthetic sunscreens

Abstract: The photoprotective capabilities of a family of synthetic MAA analogues have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 29 publications
3
59
0
Order By: Relevance
“…Of 3). 57 Their recent experiments agree with their computational findings (vida supra), and Case revealed that, following photoexcitation at the absorption maximum of the cyclohexenone core (see Figure 6), the vibrationally hot S1 state undergoes vibrational cooling, leading to population of the S1 minimum. Excited state population localised within the S1 minimum is subsequently trapped for at least 2.5 ns (a consequence of the maximum time-window of the experimental setup used by Woolley et al).…”
Section: Case Studiessupporting
confidence: 78%
“…Of 3). 57 Their recent experiments agree with their computational findings (vida supra), and Case revealed that, following photoexcitation at the absorption maximum of the cyclohexenone core (see Figure 6), the vibrationally hot S1 state undergoes vibrational cooling, leading to population of the S1 minimum. Excited state population localised within the S1 minimum is subsequently trapped for at least 2.5 ns (a consequence of the maximum time-window of the experimental setup used by Woolley et al).…”
Section: Case Studiessupporting
confidence: 78%
“…PL steady‐state measurements were recorded with a spectrophotometer (PerkinElmer Instrument LS55). The femtosecond transient absorption measurements is described elsewhere 44. Ultrashort laser pulses were generated in an oscillator‐regenerative amplifier laser system (Coherent, Mantis‐Legend) that provides a 1 KHz train of 35 fs pulses at 800 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The femtosecond transient absorption measurements is described elsewhere. [44] Ultrashort laser pulses were generated in an oscillatorregenerative amplifier laser system (Coherent, Mantis-Legend) that provides a 1 KHz train of 35 fs pulses at 800 nm. Pump pulse wavelength in the range 500-650 nm is obtained by means of sum frequency of the fundamental 800 nm and the signal beam of an optical parametric amplifier (Coherent, TOPAS), while the 400 nm is generated as the second harmonic of the fundamental beam.…”
Section: Methodsmentioning
confidence: 99%
“…Following up on their earlier theoretical and experimental work [ 89 ], Losantos et al [ 84 ] further investigated some of the UV filter candidates they previously synthesized using TEAS, fluorescence up-conversion and computational methods. The four studied molecules (9–12) can be found in Figure 14 [ 84 ]. CASPT2//CASSCF methodology [ 119 , 120 ] was implemented, similar to their previous study [ 89 ], to determine the deactivation pathway of molecule 11.…”
Section: Case Studiesmentioning
confidence: 99%
“…However, Losantos et al [ 84 ] and Woolley et al [ 85 ] have conducted such experiments on MAA motifs. In addition to these studies, complementary theoretical work has modelled the minimum energy relaxation pathways of MAAs and molecules alike, giving insight into their photoprotective mechanisms [ 84 , 86 , 87 , 88 , 89 , 90 ]. Section 2.2 of this review will primarily cover ultrafast spectroscopy and theoretical work conducted to the present date on MAAs and MAA motifs.…”
Section: Introductionmentioning
confidence: 99%